Analisis Wacana Kritis Konstruksi Konflik Keluarga dalam Film Cek Toko Sebelah - Tunziyah, Tunziyah; Ri?aeni, Ida (Universitas Serang Raya, 2019)
A film is made to represent reality from people's lives. Films can depict various dimensions of life insociety, as well as the one depicted in a comedy film titled ?Cek Toko Sebelah (CTS)'. This research usesqualitative research using discourse analysis developed by Teun Van Dijk. With the Van Dijk method,Discourse Research is not only on text alone, but also how a text is produced. The results of the researchat the text level, obtained a picture of family conflict associated with the label of the majority of Chinesecitizens who are traders. The awarding of the film title also comes from a typical idiom that is oftenraised by the Chinese when transacting with the shopper in the shop. In the level of social cognition, thisfilm shows the representation of the millennial Chinese generation, a picture of the conflict betweenchoosing a career or family, being obedient to parents and prioritizing the family. In the level of socialcontext, it seems that the trend of young people in big cities who work and pursue more careers thancontinue the tradition and family heritage as well as big businessmen are rulers who do not care aboutChinese or not Chinese. They are shown as citizens who often oppress small entrepreneurs and so on tosubmit to their interests.